What is to be done: The Enlightened Thinkers and Islamic Renaissance. By Dr. Ali Shari’ati. Edited and Annotated by Farhang Rajaee. Foreword by John L. Esposito. Houston, Texas, USA: The Institute for Research and Islamic Studies (IRIS), 1986, pp. 181. ISBN 0-932625-04-5, ISBN 0-932625- 01-0 (pbk.) - Ramdane, Tahraoui; Souad, Merah (IIUM PRESS, 2014)
This is a collection of lectures delivered by Dr. Ali Shari’ati in 1970. The quest of Shari’ati to establish an Islamic theory of change and revolution was mainly constructed on a number of main themes, including the role of intellectuals, education, reviving sciences, scientific research, and propaganda. He discussed his Islamic renaissance project from both theoretical and practical perspectives. Some of the lectures tackled the theoretical aspects of the project, including: “Where shall we began”, “What is to be done”, and “Surah al- Rum “The Roman”: A Message to Enlightened Thinkers” tackled the theoretical part of his project. Meanwhile, the lecture entitled “What is to be done: A Practical Plan for Husayniah Irshad”, which appeared in the last part of the book, presented a practical plan of action for this project.